Re-visiting soil carbon and nitrogen stocks in a temperate heathland seven years after the termination of free air CO2 enrichment (FACE) - Li, Qiaoyan; Ambus, Per Lennart; Michelsen, Anders; Schmidt, Inger Kappel; Beier, Claus; Dietzen, Christiana A.; Reinsch, Sabine; Arndal, Marie Frost; Larsen, Klaus Steenberg (Geoderma, 2022)
•Extra stored soil carbon was lost again seven years after FACE termination.•Increased soil carbon during FACE stimulated the decomposition of old soil carbon.•Large transfer of nitrogen from deeper soil layers upon increasing plant demand.•Soil carbon and nitrogen pools in this ecosystem are highly dynamic. The response of soil carbon to global climate change remains one of the largest uncertainties for future climate projection. In this study, we re-sampled the soil in a long-term, field-scale, multi-factorial climate experiment, CLIMAITE (Free Air CO2Enrichment (FACE), warming and drought in all combinations in a Danish heathland ecosystem) in 2020, seven years after the experiment was terminated. We aimed to study the dynamics of the soil carbon after the cessation of long-term multi-factorial climate manipulation, with special attention to the fate of the additional soil carbon (19% increase) that was sequestered in plots exposed to elevated CO2 concentrations (eCO2). Soil carbon pools in former eCO2 plots, as well as in drought and warming plots, had normalized again by 2020. However, the difference in soil isotopic composition between ambient and former eCO2 plots remained, indicating similar loss fractions from older and newer soil carbon pools in the eCO2 plots as well as stimulation of the decomposition of old soil carbon via priming. Throughout the study period, soil nitrogen dynamics tracked the changes in soil carbon, suggesting that nitrogen from deeper soil layers was transported upwards to meet increasing plant demand during eCO2 but was lost again from the topsoil after termination of the FACE treatment. Our findings show that the soil carbon and nitrogen pools in this ecosystem are highly dynamic and may respond strongly and rapidly to changes in major ecosystem drivers, and that revisiting climate experiments after the cessation of treatments may provide valuable insights into the dynamics, stability and resilience of major element pools in ecosystems.